Proceedings of the First International Workshop on Ontology-Supported Business Intelligence 2008
DOI: 10.1145/1452567.1452574
|View full text |Cite
|
Sign up to set email alerts
|

An ontology-based cluster analysis framework

Abstract: The main objectives of this paper are to discuss the various aspects of similarity calculations between objects and sets of objects in ontology-based environments and to propose a framework for cluster analysis in such an environment. The framework is based on the ontology specification of two core components: description of categories and description of objects. Similarity between objects is defined as an amalgamation function of taxonomy, relationship and attribute similarity. The different measures to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Ontologies allow performing the knowledge representation by means of terms and definitions about the concepts related to a given domain, promoting the representation of the semantic relationships, and not only the syntactic relationship of the data. When developing ontology it is necessary to describe the categories and objects as well as the relationships between the data involved (Lula & Paliwoda-Pękosz, 2008). Ontology has the exploration and representation capability of semantic and conceptual relationships of the terms belonging to a particular domain (Silva et al, 2009).…”
Section: Ontologymentioning
confidence: 99%
“…Ontologies allow performing the knowledge representation by means of terms and definitions about the concepts related to a given domain, promoting the representation of the semantic relationships, and not only the syntactic relationship of the data. When developing ontology it is necessary to describe the categories and objects as well as the relationships between the data involved (Lula & Paliwoda-Pękosz, 2008). Ontology has the exploration and representation capability of semantic and conceptual relationships of the terms belonging to a particular domain (Silva et al, 2009).…”
Section: Ontologymentioning
confidence: 99%
“…Therefore, it is not surprising that the relationship between metadata and ontology has drawn researchers' attention for quite some time; for example, a recent case study of constructing ontology from metadata in the weather domain was reported (Chen & Plale, 2012). In particular, the uses of metadata and ontologies for document clustering and analysis have been addressed from various perspectives (e.g., Wong et al, 2003;Lula and Paliwoda-Pekosz, 2008).…”
Section: Relevance Of Metadata and Ontology To Document Clusteringmentioning
confidence: 99%
“…Our approach utilizes both content-based and collaborative filtering. The crucial point in this study is that the contentbased filtering in our approach uses semantic similarity measures on ontology-based metadata, based on the studies in (Maedche and Zacharias, 2002) and (Lula and Paliwoda-Pekosz, 2008), instead of naive Bayesian classifier (Mitchell, 1997) which is mentioned in (Melville et al, 2002). After that, collaborative filtering is performed using enhanced data to overcome over-specialization problem in contentbased filtering.…”
Section: Introduction and Related Workmentioning
confidence: 99%